IORT for early-stage, low-risk breast cancer: Outcomes from a prospective, observational study - Amalia Palacios-Eito; María del Carmen Moreno-Manzanaro; María Espinosa-Calvo; Fátima Ginés-Santiago; Juan Adrián Camús-Martínez; Ángel Calvo-Tudela; Pilar Rioja-Torres; Sara Romero-Martín; José Antonio Miñano-Herrero; Gustavo R. Sarria; Sonia García-Cabezas (Clinical and Translational Radiation Oncology)
Introduction: Treatment of early-stage, low-risk breast cancer (BC) has undergone significant de-escalation during the past years. The TARGIT-A trial provided information on intraoperative radiotherapy (IORT) as a convenient, single-fraction modality. Nevertheless, significant discussion regarding different aspects of the trial continues. This study reports on oncological outcomes in a real-world clinical setting and contributes to the understanding of its optimal indication. Methods: Five-hundred patients planned for breast-conserving surgery (BCS) were screened for IORT between June 2017 and December 2023, within this prospective, observational, single-center. The treatment protocol replicated the experimental arm of the TARGIT-A trial, implementing stricter inclusion criteria and maintaining a risk-adapted approach. The primary endpoint was ipsilateral breast recurrence rates (IBR). Secondary endpoints included local recurrence-free survival, progression-free survival, overall survival, and patient-reported cosmesis. The Kaplan-Meier method was used to analyze survival and recurrence risk, and risk factors for IBR were assessed through Cox regression analysis. Results: After screening and recruiting, IORT was performed in 464 patients. The median follow-up was 45.3 (8–89) months. The estimated 5-year IBR risk in the entire cohort was 1.7 % (95 % CI: 0.7 %–2.8 %), decreasing to 1 % (95 % CI: 0.3 %–2.4 %) in the IORT + whole breast irradiation (WBI) cohort. In the IORT-only cohort, the risk was 2.1 % (95 % CI: 0.6 %–3.7 %). No significant differences were observed among the three subgroups. The 5-year overall survival and breast cancer-specific survival rates were 97.6 % (95 % CI: 96.0 %–99.1 %) and 99.5 % (95 % CI: 98.5 %–100 %), respectively. Two independent significant risk factors for IBR were identified: age < 50 years (HR = 0.138, 95 % CI: 0.032–0.597, p = 0.008) and close or affected surgical margins (HR = 5.8, 95 % CI: 1.5–22.5, p = 0.011). No grade 3–4 toxicity events were reported. Patient-reported cosmesis was excellent/good in 84 % of cases. Conclusions: Local recurrence rates were low amongst all groups. Superior control outcomes could be obtained by applying more restrictive criteria than the TARGIT A trial. Longer follow-up is needed to confirm our findings.